Design and implementation of a university-based COVID-19 testing programme: an observational study. (November 2021) - Blackmore, Claire; Hall, Gareth W; Allsopp, Rebecca C; Hansell, Anna L; Cowley, Caroline M; Barber, Ruth C; Holmes, Christopher W; Tobin, Martin D; Shaw, Jacqui A; Brunskill, Nigel J; Baker, Philip N
Abstract: Background: Little is known about how asymptomatic testing as a method to control the transmission of COVID-19 can be successfully implemented, and the prevalence of asymptomatic infection within university populations. The aim of this study was to describe the methodology of implementing a novel asymptomatic mass testing programme, and to report the number of positive cases diagnosed during the study period. To our knowledge, this study is the first to report prevalence of asymptomatic COVID-19 infection within a UK university population using reverse transcriptase loop-mediated isothermal amplification (RT-LAMP) as a molecular diagnostic tool. Methods: An observational study was undertaken to describe the set-up and implementation of a novel COVID-19 testing programme on a UK university campus between Sept 28 and Dec 18, 2020. Students and staff members volunteered for testing throughout the term. The programme used RT-LAMP testing to identify asymptomatic cases within the population. Any positive cases received RT-PCR testing to confirm the result using the current gold-standard testing methodology. Findings: 1673 tests were done using RT-LAMP during the study period, of which nine were positive for COVID-19. This gave an overall positivity rate of 0·54%, equivalent to a rate in the tested population of 538 cases per 100 000 over the duration of testing. All positive tests were also found to be positive on RT-PCR testing, giving a false positive rate of 0%. Uptake was affected by changes to delivery of university teaching, leading to lower attendance on campus throughout the term. Interpretation: This study shows that it is possible to rapidly set up a universal university testing programme for COVID-19 in collaboration with local health-care providers using RT-LAMP testing, with full concordance between RT-LAMP testing and RT-PCR testing on positive RT-LAMP results. Positive results were similar to those in the local population, although with a different weekly peak of infection. Funding: None.